Neoliberal Veridiction: An Analysis of the Effects of Neoliberal Regimes of Truth in Producing the Self (Nóema, 2022)
Starting from the thesis that in neoliberalism a practice of government of others is at work and it iscarried out through the solicitation of a particular way of government of oneself, in this contributionwe will try to consider the specific regime of truth that emerges in relation to this form of exercise ofpower. To understand this declination of veridiction as a technique of the self capable of ensuring thegovernment of others, this paper will be developed in three parts. At first, an attempt will be made todefine the notion of a regime of truth so that we can understand its significance in relation to neoliberalgovernmentality. In this way it will be possible, at a later stage, to analyze the neoliberal regime of truthby defining its functioning and its targets. We will consider, finally, the effects that these veridictionalpractices generate in the processes of subjectivation to the extent that they produce the individual as anentrepreneur of oneself, whose choices and behaviors have to be guided by the logic of human capital.
Keywords: Neoliberalism; Michel Foucault; human capital; regime of truth; governamentality; entrepreneur of the self; techniques of the self